2020
DOI: 10.3389/fvets.2020.00412
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Production Parameters, Egg Qualities, Fecal Volatile Fatty Acids, Nutrient Digestibility, and Plasma Parameters in Laying Hens Exposed to Ambient Temperature

Abstract: The present study was undertaken to investigate the impact of heat stress on nutrient digestibility and tibia and reproductive traits, and changes in laying performance, egg qualities, fecal volatile fatty acids, and plasma parameters in laying hens. One-hundred twenty 52-week-old laying hens were raised in three temperature-controlled facilities with constant humidity (50% RH), either normal temperature (LT; 22 • C) or heat stress considered being moderate (MT; 27 • C) or severe (HT; 32 • C) for 42 days. Feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 34 publications
4
26
0
1
Order By: Relevance
“…However, the earlier study reported that laying hens housed at 30ºC vs. 24ºC performed less and exhibited altered nutrient digestibility [20]. Similarly, we observed the negative effect of heat stress on laying hens when they were exposed to 32ºC vs 27ºC [21]. In addition, temperature and RH that were reached to target range (LH75 and HL75) maintained continuously throughout the experiment, which might be more stressful to hens than cyclic or intermittent regimes.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, the earlier study reported that laying hens housed at 30ºC vs. 24ºC performed less and exhibited altered nutrient digestibility [20]. Similarly, we observed the negative effect of heat stress on laying hens when they were exposed to 32ºC vs 27ºC [21]. In addition, temperature and RH that were reached to target range (LH75 and HL75) maintained continuously throughout the experiment, which might be more stressful to hens than cyclic or intermittent regimes.…”
Section: Discussionsupporting
confidence: 62%
“…It is well known that laying hens exposed to heat stress lower feed intake to minimize heat production, and change blood flow from organs to body surface area to dissipate sensible heat [3]. In addition, heat stress impairs the ovarian function by lowering ovarian weight and number of large follicles [6,21,24].…”
Section: Discussionmentioning
confidence: 99%
“…However, an earlier study reported that laying hens housed at 30 °C had a poor performance and exhibited altered nutrient digestibility [ 23 ] compared to hens housed at 24 °C. Similarly, we observed a negative effect of heat stress on laying hens when they were exposed to 32 °C vs. 27 °C [ 24 ]. Thus, the selected response indicators (i.e., performance, egg quality, serum parameters, and stress indicators) could have been altered if temperature, but not RH, played an essential role in influencing the performance, behavior, or physiology of laying hens in this study.…”
Section: Discussionmentioning
confidence: 92%
“…It has been established that laying hens exposed to heat stress reduce feed intake to minimize heat production and change blood flow from the organs to the body surface area to dissipate sensible heat [ 4 ]. In addition, heat stress impairs ovarian function by lowering ovarian weight and the number of large follicles [ 7 , 24 , 28 ] as well as plasma concentrations of minerals, including calcium, magnesium, and phosphorus [ 24 ]. As observed in this study, none of the environmental treatments affected blood biochemical parameters, indicating that neither environmental regime affected heat stress’s physiological indicators in laying hens.…”
Section: Discussionmentioning
confidence: 99%
“…This affects the productive qualities of poultry, including growth processes, reproductive abilities and egg production, and product quality. [1,3,5,6], as a result of the predominant direction of the body's energy resources to the course of adaptation processes [7]. In addition, heat stress leads to an increase in the morbidity and mortality of poultry [8].…”
Section: Introductionmentioning
confidence: 99%